Collaboration in scientific research : the views and practices of researchers in the College of Sciences, Massey University, Turitea campus : a case study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Business Administration (DBA) at Massey University, Wellington, New Zealand - Emerre, Margaret (Massey University, 2013)
Collaboration in scientific research has been increasing steadily for the last thirty years and it now characterises scientific research world-wide. New Zealand is part of this trend and this study looks at the collaboration in scientific research in one tertiary institution in New Zealand. As a mixed methods study it incorporates a survey of researchers and a number of semi-structured interviews. The researchers who participated in the study cover the full array of science disciplines and range in experience from early to late career researchers. Information on the institutional context has been gathered from the university’s key strategic plan, The Road to 2020, and from an interview with the Assistant Vice-Chancellor, Research & Enterprise, and the perspective of the funding agencies comes from interviews with senior officers of the four main research funding agencies. The findings suggest that researchers collaborate for a variety of reasons: for personal reasons because they enjoy working with others; for tactical reasons to increase the probability of getting funding; but overall they collaborate to get better outcomes. The funding agencies promote collaboration for quite different reasons. For them it is a mechanism to promote quality, to augment the science sector, and to ensure that New Zealand researchers can work with the best that the world has to offer. New Zealand researchers are members of an international community of scientific researchers and are active participants in what Martin Lord Rees calls the “unending quest of science; as its frontiers advance, new mysteries come into focus just beyond those frontiers” (p. 469, 2010). Just as the quest of science continues, the quest for understanding how “science is done” and finding new ways of “doing science” continues. Collaborating in research is one of those ‘new ways’ and whilst collaboration is now ubiquitous, the process of collaboration has not received a great deal of attention in the literature. As resources become leaner and demands for accountability stronger, there is a renewed interest in areas such as research competencies, the initial training of researchers and subsequent professional development, the composition of a research team, leadership of research teams, and management of research projects. This thesis concludes with a set of recommendations for researchers.
Keywords: Scientific research; College of Sciences, Massey University; Collaborative research; Researchers; Road to 2020; Massey University research